Environmental Impact Assessment of Tehran- Karaj Highway by Using Plants Indicators (Journal of University of Babylon for Engineering Sciences, 2018)
Lead pollution is one of the negative impacts of roads on environment, which can be assessed using environmental impact assessment. As a study case, Tehran- Karaj highway was selected for studying environmental lead pollution in pine tree needles (plants indicators). Samples were collected from seven stations and five distances (0, 10, 20, 50, 100 meter). The results showed that transport has a direct effect on lead pollution in trees. The differences in lead concentrations were significant for both stations and distances. The average lead concentration was 11.34 mg/Kg in the station close to Tehran, and 3.8 mg/Kg in the closest station to Karaj. This is because heavier transfer and higher density of cars in Tehran compared to Karaj. The average Pb concentrations in the stations besides the highway was 8.77 mg/Kg and decreased to 6.57 mg/kg in stations located in 100 meter away from the highway. While the average Pb concentration in station E was 1.53 mg/Kg, it was decreased constantly in all distances, due to tree coverage. A conclusion, the analytical method of roads environmental impact assessment can be used effectively for monitoring Pb pollution. The pollution can be decreased by using pine trees and emphasis on using windbreakers.